2008
DOI: 10.1016/j.mce.2008.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of olanzapine on glucose transport, proliferation and survival in C2C12 myoblasts

Abstract: Please cite this article as: Tulipano, G., Spano, P.F., Cocchi, D., Effects of olanzapine on glucose transport, proliferation and survival in C2C12 myoblasts, Molecular and Cellular Endocrinology (2007), doi:10.1016/j.mce.2008 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…In control experiments, insulin stimulated uptake to a moderate degree, as noted by others (Iwata et al, 2009; Tulipano et al, 2008). As expected cytochalasin B (a cell trafficking and GLUT-4 translocation inhibitor) and LY294002 (a PI3K inhibitor) reversed insulin mediated uptake (Fig.…”
Section: Resultssupporting
confidence: 82%
“…In control experiments, insulin stimulated uptake to a moderate degree, as noted by others (Iwata et al, 2009; Tulipano et al, 2008). As expected cytochalasin B (a cell trafficking and GLUT-4 translocation inhibitor) and LY294002 (a PI3K inhibitor) reversed insulin mediated uptake (Fig.…”
Section: Resultssupporting
confidence: 82%
“…1a). We checked unspecific drug toxicity by using Trypan Blue exclusion assay, an index of cell necrosis, as described [27]. AICAR (0.5 mM) or Compound C (2 lM) did not affect the cell membrane permeability to Trypan Blue compared with control cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…After centrifugation, the resulting supernatants were subjected to Western blotting. The exhaustive description of the methods have been reported previously [27]. Gel-Pro analyzer 3.1 software was used to quantify protein bands detected on western blots.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Other studies have shown GLUT4 enhancement under different concentrations of cinnamon extract or dihydrocinnamic acid (DHH105), a derivative of cinnamon, on GLUT4 content in animal adipose tissue [17] or 3T3-L1 cell line, a good model for studding fat tissue metabolism [14]. But muscular tissue is the most important site for glucose metabolism which uses more than 75 % of body glucose expenditure under insulin impact [18][19][20][21]. As the rate limiting step of blood glucose level expenditure is regulated by GLUT4 glycoprotein presence in the cytoplasmic membrane [22,23], the objective of current study was to investigate the effect of cinnamon water extract on GLUT4 contents of cytoplasmic membrane (CM) and nuclear/endoplasmic (N/ER) reticulum fractions of differentiated C2C12 myotubes.…”
Section: Introductionmentioning
confidence: 99%